The Factors Affecting Purchasing Decision through Pegipegi Application by Customers of Dian Nuswantoro University - Diana Aqmala; Febrianur Ibnu Fitroh Sukono Putra; Dian Yustika Rini (Journal of Management and Entrepreneurship Research, 2020)
Objective: This study aims to analyse the factors that influence online purchasing decisions through Pegipegi application.Research Design & Methods: This research method is quantitative with sample of 170 respondents of students of Universitas Dian Nuswantoro. The sample collecting technique is purposive sampling through questionnaires distributed personally using Likert scale. The technique of Analysis used is structural equation model. Findings:The finding results showed that 1) Electronic Word of mouth has a significant direct effect on purchasing, 2) price perception has a direct effect on purchasing decisions, 3) product quality has a direct effect on purchasing decisions, 4) brand awareness is able to mediate the influence of electronic word of mouth, price perception, and product quality on purchasing decisions.Implications & Recommendations:This research has managerial implications for the marketing policies implemented by the Pegipegi application in order to increase customer awareness, thereby increasing the desire to immediately make purchasing decisions when they need appropriate service products.Contribution & Value Added:This study provides a positive contribution to decision making on marketing policies in order to increase market share and company competitiveness in the industry.